New records of the golden jackal (Canis aureus L.) in the upper Soča valley, Slovenia - Miha Mihelič; Miha Krofel (Natura Sloveniae)
Golden jackals (Canis aureus) have been recorded in the Slovenian Julian pre-Alps for more than 50 years. In recent years, however, a substantial increase in sightings of golden jackalshas been recorded in the area around the town of Bovec. During the present study we gathered information through interviews with local hunters and other residents and conducted a basic questionnaire on their opinion about this expanding carnivore. In addition, we performed monitoring of jackals with the use of acoustic playback method, photo-traps and searching for footprints and other signs of jackal presence. We also reviewed the database of the reported jackal depredations on livestock at the Bovec Forest Service. In total, we conducted 31 interviews and gathered information on 100 records of jackal presence from 2009 to 2012. The questionnaire showed a negative attitude toward jackal among local hunters. Using acoustic methods, we were unable to confirm the presence of a territorial jackal group, but we did detect jackals on 26 photographs made with photo-traps at one location. During the study, two jackals were killed by car and we collected tissue samples for potential future genetic analysis. Official records of depredations showed high increase in assumed jackal attacks on sheep, but we could not confirm if or how many of these depredations were actually caused by jackals. Further studies are needed to understand the real extent of jackal predation on domestic and wild ungulates, as well as the origin and development of this new jackal group(s) in the Julian pre-Alps.